Le recours au français langue maternelle dans les praxéologies des professeurs des écoles en séances de langue vivante étrangère - Jessyca Tretola (Nantes Université, 2019)
This research relies on the use of the French native language by elementary school teachers during foreign language lessons. It falls within a clinical and a comparative approach. It proposes to analyze and compare the teachers'praxeologies according to the knowledge they have of the foreign language they teach, leaning on the didactics of the foreign languages, on the Anthropological theory of Didactics, on the Common European Framework of Reference for languages and on school programs. The results of the analysis allow us to conclude that the less qualified teachers, in the foreign language they teach, do not often use the native language and metalanguage during their lessons, compared to the most qualified teachers.